Partial Body Mass Recovery After Caloric Restriction Abolishes Improved Glucose Tolerance in Obese, Insulin Resistant Rats - Cornejo, Manuel A.; Nguyen, Julie; Cazares, Joshua; Escobedo, Benny; Nishiyama, Akira; Nakano, Daisuke; Ortiz, Rudy M. (Frontiers in Endocrinology, 2020)
Caloric restriction, among other behavioral interventions, has demonstrated benefits on improving glycemic control in obesity-associated diabetic subjects. However, an acute and severe intervention without proper maintenance could reverse the initial benefits, with additional metabolic derangements. To assess the effects of an acute caloric restriction in a metabolic syndrome model, a cohort of 15-week old Long Evans Tokushima Otsuka (LETO) and Otsuka Long Evans Tokushima Fatty (OLETF) rats were calorie restricted (CR: 50% x 10 days) with or without a 10-day body mass (BM) recovery period, along with their respective ad libitum controls. An oral glucose tolerance test (oGTT) was performed after CR and BM recovery. Both strains had higher rates of mass gain during recovery vs ad lib controls; however, the regain was partial (ca. 50% of ad lib controls) over the measurement period. Retroperitoneal and epididymal adipose masses decreased 30% (8.8 g, P<0.001) in OLETF; however, this loss only accounted for 11.5% of the total BM loss. CR decreased blood glucose AUC 16% in LETO and 19% in OLETF, without significant decreases in insulin. Following CR, hepatic expression of the gluconeogenic enzyme, PEPCK, was reduced 55% in OLETF compared to LETO, and plasma triglycerides (TG) decreased 86%. Acute CR induced improvements in glucose tolerance and TG suggestive of improvements in metabolism; however, partial recovery of BM following CR abolished the improvement in glucose tolerance. The present study highlights the importance of proper maintenance of BM after CR as only partial recovery of the lost BM reversed benefits of the initial mass loss.